2005
DOI: 10.1007/s11084-005-5760-3
|View full text |Cite
|
Sign up to set email alerts
|

The Last Common Ancestor: What's in a name?

Abstract: Twenty completely sequenced cellular genomes from the three major domains were analyzed using twice one-way BLAST searches in order to define the set of the most conserved protein-encoding sequences to characterize the gene complement of the last common ancestor of extant life. The resulting set is dominated by different putative ATPases, and by molecules involved in gene expression and RNA metabolism. DEAD-type RNA helicase and enolase genes, which are known to be part of the RNA degradosome, are as conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 55 publications
2
59
0
Order By: Relevance
“…Thus, the evolution by merging with other sub-system may have originated more complex organisms, which in turn led directly to appearance of LUCA. Delaye et al 2005, through the analysis of universally conserved pathways, proposed a group of proteins that could be composing the genome of LUCA. Analysing the results obtained by Delaye et al (2005), we observed that several proteins proposed as participants in the composition of LUCA are also in our data set, which shows the consistency of our data with independent methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the evolution by merging with other sub-system may have originated more complex organisms, which in turn led directly to appearance of LUCA. Delaye et al 2005, through the analysis of universally conserved pathways, proposed a group of proteins that could be composing the genome of LUCA. Analysing the results obtained by Delaye et al (2005), we observed that several proteins proposed as participants in the composition of LUCA are also in our data set, which shows the consistency of our data with independent methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Delaye et al 2005, through the analysis of universally conserved pathways, proposed a group of proteins that could be composing the genome of LUCA. Analysing the results obtained by Delaye et al (2005), we observed that several proteins proposed as participants in the composition of LUCA are also in our data set, which shows the consistency of our data with independent methodologies. These similarities could indicate that these proteins pertained to an era prior to LUCA and that these metabolic systems were gradually being mounted through cooperative processes among progenotes.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of sets of highly conserved sequences that may have been part of the gene complement of the last common ancestor (Harris et al 2003;Delaye et al 2005) shows that they are surprisingly rare among enzymes involved in nucleotide metabolism, as well as among those involved in polymerization, translation, transcription, and RNA processing and degradation. The few cases of FeS protein foldenzymes associated with nucleic acid synthesis and processing include (a) the (eu)bacterial endonuclease III, which is involved in DNA repair (Cunningham et al 1989); (b) the Sulfolobus solfataricus DNA-dependent RNA polymerase, where the Fe-S cluster is removed from the catalytic site and probably plays a structural role (Hirata and Murakami 2009); and (c) the eukaryotic and archaeal DNA primase endowed with a [4Fe-4S] cluster that appears to have a regulatory role (Weiner et al 2007;Klinge et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The best known of these genes is the 16S rRNA, traditionally used for phylogeny. In this manner, comparative studies serve mainly evolutionary biology and the quest for the LUCA's constitution (132).…”
Section: Comparative Approachmentioning
confidence: 99%